DEVELOPING THE CONCEPTUAL APPARATUS OF COMMERCIAL CREDITING - Elena A. Erina (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article analyzes the conceptual apparatus of the commercial credit for organizations. The author shows key types of trade credits, provisions of credit policy of the enterprise, the system of this policy administration, the model of using commercial credit - a potential borrower which is applied in the international practice for commercial organizations. The author puts forward a specified and more generalized notion of the commercial credit as a special form of the credit made up according to the credit contract or other agreements between sellers and buyers of the B2B system as selling goods (jobs, services) by installment and with delayed payment (credit).